Dampak Sosial Ekonomi Rencana Tata Ruang Wilayah Kabupaten Pandeglang Tahun 2011-2031 Terhadap Sektor Pertanian : Studi kasus Kecamatan Cimanuk Kabupaten Pandeglang - Susvia Delta Kusdiane; Agus Sjafari; Suwaib Amiruddin (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2022)
Agriculture is one of the top sectors that help to increase regional development in the Pandeglang regency. Based on this fact, the local government made spatial plans for 201-2031. One of the goals is to maintain the availability of agricultural land in the Pandeglang Regency outside of the LP2B policy. However, along with this policy, the impact of socio-economic in society has not been maximized. This study aims to see how the effect of the regional spatial plans of Pandeglang Regency on the socio-economics of farming communities, especially in Cimanuk District—using qualitative methods with a descriptive approach. The results of this research are that the implementation of the Pandeglang Regency spatial plans is in accordance with the existing objectives but has not been able to maintain the sustainability of the agricultural sector and has not provided a maximum positive impact on the socio-economic of the local community, especially for the farming community in Cimanuk District. This can be seen from the unstable increase in household welfare of the farming community, fluctuating health level, the decrease in the number of unemployed people is still not maximal, etc.